2012
DOI: 10.1128/jcm.00652-12
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Detection of Rifabutin-Susceptible Mycobacterium tuberculosis

Abstract: Rapid assays are still needed to detect rifabutin (RFB) susceptibility for proper tuberculosis treatment. To assess the use of the GenoType MTBDRplus assay and subsequent rpoB gene sequencing on detection of RFB susceptibility, we analyzed 800 multidrug-resistant Mycobacterium tuberculosis isolates, and 13% (104/800) were RFB susceptible. Of the 104 RFB-susceptible isolates, 71 (68.3%) isolates were rapidly identified using two molecular assays, while the remaining isolates could be determined using convention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 9 publications
0
15
2
Order By: Relevance
“…In these studies, the most common mutations associated with RIF resistance/RFB susceptibility were associated with residues 516, 529, and 533. In our study, the proportion of RIF-resistant isolates that were RFB susceptible was only slightly higher than the proportions reported elsewhere (28%) (7,28,29). Mutations H526L, F514FF, D516V, and S522L were all associated with RIF resistance/RFB susceptibility patterns.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…In these studies, the most common mutations associated with RIF resistance/RFB susceptibility were associated with residues 516, 529, and 533. In our study, the proportion of RIF-resistant isolates that were RFB susceptible was only slightly higher than the proportions reported elsewhere (28%) (7,28,29). Mutations H526L, F514FF, D516V, and S522L were all associated with RIF resistance/RFB susceptibility patterns.…”
Section: Discussioncontrasting
confidence: 44%
“…Previous studies have shown a proportion of RIF-resistant isolates with susceptibility to RFB ranging from 13 to 26% (7,28,29). In these studies, the most common mutations associated with RIF resistance/RFB susceptibility were associated with residues 516, 529, and 533.…”
Section: Discussionmentioning
confidence: 61%
“…However, RIF-resistant strains possessing certain mutations, mostly in codons 511, 516, 518, 522, 526, 533 may retain a level of in vitro susceptibility to RFB depending on the particular amino acid substitutions and have the potential to be clinically effective against RIF-resistant MTBC strains (11 – 21). Utilization of molecular assays capable of discriminating SNPs in the RRDR at the nucleotide level may allow for the prediction of culture-based drug susceptibility testing (CDST) results to RIF and RFB (14 – 15, 21 – 24). Owing to increased use of molecular diagnostics for detection of RIF resistance, an understanding of the relationship between different rpoB mutations and their association with differential resistance levels may be helpful to clinicians treating RIF-resistant TB or MDR-TB as a real-time complement to CDST which can take weeks to be completed.…”
Section: Introductionmentioning
confidence: 99%
“…Studies from low HIV settings have reported that 13–26% of MDR-TB isolates show sensitivity to RFB (Chen et al, 2012; Jo et al, 2013; Schon et al, 2013). However, there is limited information on the frequency of RFB susceptibility among MDR-TB isolates in an HIV endemic region.…”
Section: Introductionmentioning
confidence: 99%